Saturday Night Live - The Complete First Season Episode 1-24 - Wilson, Dave; Brooks, Albert; Aykroyd, Dan; Belushi, John; Oz, Frank (Universal, 2007)
A late-night comedy show featuring several short skits, parodies of television commercials, a live guest band, and a pop-cultural guest host each week. Many of the SNL players have spun off successful independent comedy and/or movie careers from here. [www.play.com]